PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG DI CURUG LEUWI HEJO - Taufiq Kurniawan; M. Fajri Gifar Muqtabar (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
The development of technology and communication has led to an increase in the use of social media in Indonesia as a promotional tool. One example is the use of Instagram by the management of Curug Leuwi Hejo tourist attraction. The purpose of this research is to determine the influence of Instagram social media promotion on visitors' decisions to visit Curug Leuwi Hejo. This research uses a quantitative approach with a sample size of 100 respondents. The sampling method used is purposive sampling, which means the respondents are active Instagram users who have visited Curug Leuwi Hejo tourist attraction. Based on the regression analysis, the results show a p-value of 0.000. This value is smaller than the alpha of 0.5 or 5%, indicating that there is an influence of Instagram social media on visitors' decisions to visit Curug Leuwi Hejo. Therefore, the conclusion of this study is that Instagram social media promotion has a significant impact on visitors' decisions to visit Curug Leuwi Hejo. The managerial implication based on the above conclusion is that the management of Curug Leuwi Hejo tourist attraction needs to improve its promotion activities on Instagram by creating good, attractive, and informative content.